Application of Hansen Dolubility Parameters to ExtractionProcess of Phenolic Compounds from Chamomile Inflorences - Zieliński, R. (Scientific Journal of Gdynia Maritime University, 2017)
The aim of this work was to determine a practical usefulness of literature Hansen solubility parameters to determine the composition of solvents for efficient extraction of activecompounds present in chamomile inflorescences. The Hoy's method was used to compute the components of the Hansen solubility parameters for mixtures of solvents and for some model phenolic compounds present in this plant material. The numerical values of the parameters obtained in such a way for mixtures of two components systems: water – ethanol, were presented using Bagley’s plot. It was assumed that the condition for a correct selection of the extrahent mixture is the distance on the Bagley's plot below 5 MPa(1/2) between the mixture of solvents and the extracted component. On this basis the optimum composition of the used solvents was found. This result was verified for the extraction process of polyphenolic compounds present in chamomile inflorescences. It was shown experimentally that in case of chamomile inflorescences the extrahent composition determined in such a way leads to obtainment of extracts with a high content of polyphenolic compounds.